REVIEW AN IMPROVEMENT ON TECHNICAL OPERATION IN DRINKING WATER SYSTEM FOR WATER SUPPLY STATION (Journal of Engineering, 2009)
Water plays a strategic role in the development of many facilities in our country. Still, the biggest construction projects in the world take place in Iraq with the creation of the most ambitious architectural centers. Great water production plants and distribution networks are constructed and management of available water resources is an important issue. This paper includes the identification of the hazards and introduction of control points that serve to minimize these potential hazards that providing more effect control for drinking water quality. We can conclude that end-product testing is a reactive rather than preventive way to demonstrate confidence in good and safe drinking water. This justifies the need for the formulation of a new approach in drinking water Quality Control QC based on understanding of system defense reduces for contamination and on preventive means and actions necessary to guarantee the safety of the water supplied to the consumer. Water safety plan WSP is a concept for risk assessment and risk management throughout the water cycle from the catchments to the point of consumption. This work outline and presents an overview of the first year occurrences in the developing and implementing a WSP in the multi- municipal water supply system for a city area of Baghdad. Since key personnel had contributed to the assessment of hazards and evaluation of corrective actions for control points, a greater understanding of water QC and improvements on technical operation and performance have been register, demonstrating good value for the methodology